SYMBOLS IN WILLIAM FAULKNER’S SHORT STORY “A ROSE FOR EMILY”: A SEMIOTICS APPROACH - Eka Wilany (CAHAYA PENDIDIKAN, 2016)
Semiotics, as a study about a sign as part of social life, leans on the rule or social code in a society. A rose for Emily is a short story tells about the detail of the story that has in Emily’s life and an odd relationship with her father, her boyfriend, Jefferson City, and her terrible secret that she was hiding. The objective of the article was to describe symbols used in the short story. The data was analyzed by using semiotics approach. It was found that there are some symbols in the short story illustrated by the author. They are “The Rose, The Move of her Hair, Ticking of Watch, The House and Black Color”. The Rose was symbolized as the relationship of Emily and her father. Emily grew up in luxurious. And The move of her hair was as a symbol of changing of her life. Moreover, ticking of watch was as a symbol to come to the new generation. Both of the House and Emily have changed after the death. Her house extinct as abandoned. Lastly, the black color was a symbol of death, depression, and darkness.The writer found that each symbols in A Rose for Emily illustrated the darkness and mysterious life of Miss Emily. Each of the symbols helps the author to create the story.Keywords: Semiotics Approach, , Symbol, and Short Story